Modulation of cellular redox environment as a novel therapeutic strategy for Parkinson's disease. (13th June 2022) - Deus, Cláudia M.; Teixeira, José; Raimundo, Nuno; Tucci, Paolo; Borges, Fernanda; Saso, Luciano; Oliveira, Paulo J.
Abstract: Parkinson's disease (PD) is an incurable neurodegenerative movement disorder. PD affects 2% of the population above 65 years old; however, with the growing number of senior citizens, PD prevalence is predicted to increase in the following years. Pathologically, PD is characterized by dopaminergic cell neurodegeneration in the substantia nigra, resulting in decreased dopamine levels in the nigrostriatal pathway, triggering motor symptoms. Although the pathological mechanisms leading to PD are still unclear, large evidence indicates that oxidative stress plays an important role, not only because it increases with age which is the most significant risk factor for PD development, but also as a result of alterations in several processes, particularly mitochondria dysfunction. The modulation of oxidative stress, especially using dietary mitochondriotropic antioxidants, represents a promising approach to prevent or treat PD. Although most mitochondria‐targeted antioxidants with beneficial effects in PD‐associated models have failed to show any therapeutic benefit in clinical trials, several questions remain to be clarified. Hereby, we review the role played by oxidative stress in PD pathogenesis, emphasizing mitochondria as reactive oxygen species (ROS) producers and as targets for oxidative stress‐related dysfunctional mechanisms. In addition, we also describe the importance of using dietary‐based mitochondria‐targeted antioxidants as a valuable strategy to counteract the deleterious effects of ROS in pre‐clinical and/or clinical trials of PD, pointing out their significance to slow, and possibly halt, the progression of PD.